2012
DOI: 10.1083/jcb.201111141
|View full text |Cite
|
Sign up to set email alerts
|

The Trim39 ubiquitin ligase inhibits APC/CCdh1-mediated degradation of the Bax activator MOAP-1

Abstract: Trim39 inhibits the ability of APC/CCdh1 to ubiquitylate and promote the degradation of MOAP-1, leading to enhanced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 23 publications
(29 reference statements)
4
40
0
Order By: Relevance
“…Recently, TRIM39 has been shown to stabilize modulator of apoptosis 1 (MOAP-1) by suppressing its polyubiquitylation process mediated by the anaphase promoting complex (APC/C) Cdh1 (1,2). In agreement with the proapoptotic role of MOAP-1, TRIM39 was found to enhance apoptosis in response to high-dose etoposide treatment in HEK293T cells.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Recently, TRIM39 has been shown to stabilize modulator of apoptosis 1 (MOAP-1) by suppressing its polyubiquitylation process mediated by the anaphase promoting complex (APC/C) Cdh1 (1,2). In agreement with the proapoptotic role of MOAP-1, TRIM39 was found to enhance apoptosis in response to high-dose etoposide treatment in HEK293T cells.…”
supporting
confidence: 54%
“…Notably, MOAP-1 was recently reported as a substrate of the APC/C Cdh1 ubiquitin ligase. TRIM39 was proposed to regulate MOAP-1 via acting on APC/C Cdh1 (1). Unfortunately, the molecular mechanisms underlying TRIM39-dependent regulation of APC/C Cdh1 are obscure.…”
Section: Discussionmentioning
confidence: 99%
“…3A). MST2, a core component of the Hippo signaling pathway, regulates cell proliferation, growth and apoptosis [14], and the E3 ubiquitinprotein ligase TRIM39 has a pro-apoptotic effect by inhibiting APC/CCdh1-mediated poly-ubiquitination [26]. Therefore, we mutated the miR-155-binding site resides in the 3′UTR of the MST2 and TRIM39 mRNAs and performed luciferase reporter assays using a miR-155 mimic and a miR-155 inhibitor (Fig.…”
Section: Mst2 Is a Direct Target Of Mir-155 In Vsmcsmentioning
confidence: 98%
“…Recently, we reported that involvement of the tripartite motif 39 (Trim39) E3 ubiquitin ligase in controlling DNA damageinduced apoptosis through inhibition of the anaphase promoting complex (APC/C), a multiprotein ubiquitin ligase that controls multiple cell cycle regulators, including cyclins, geminin, and others (5). Surprisingly, analysis of cell cycle progression in cells lacking Trim39 now suggests that it also might be important for G1/S progression/initiation of DNA replication in some cell types but that a target other than the APC/C was likely involved.…”
mentioning
confidence: 99%